Combination Therapy of Sorafenib and Transarterial Chemoembolization in Management of Hepatoma - Bhanu S Kumar; Andri Sanityoso; Ari Fahrial Syam; Rino Alvani Gani (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2013)
Incidence of hepatocellular carcinoma (HCC) continues to increase in developing countries and rank 5th in male and 7th in female. Main cause being reported is chronic hepatitis B in Asian region. Treatment of choice for HCC is liver resection, however it is oftenly not possible to be performed as the disease has entered advanced stage. Due to the less choice of treatment in HCC, one of the several other alternatives has been considered is transarterial chemoembolization (TACE) which is applied in patients who cannot undergo resection or ablation therapy, failure of therapy. However limitation of TACE is very high recurrence rate of HCC. Sorafenib is ananti-angiogenic medicine approved as first systemic drug in HCC therapy. Several studies stated the benefits of combination therapy of TACE and Sorafenib administration to prevent HCC recurrence. Success rate of thiscombination therapy reaches control disease rate of 100% based on response evaluation criteria in solid tumors (RECIST) from European Association for the Study of the Liver (EASL).Keywords: TACE, sorafenib, liver cancer, HCC